Explanations or advice: The impact of financial literacy on information acquisition behavior - Julia Sprenger (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
The current study examines individual decision making in the fi eld of personal finance. How do people arrive at a financial decision? A laboratory experiment investigates the way external information is integrated into the decision making process. The objective is to explore the link between financial literacy and information acquisition behavior. The results show that participants with low financial literacy generally try to compensate for their low decision-specific knowledge with a higher demand for external information but give up this strategy when the information environment is restricted to impersonal information. For female participants, low financial literacy increases demand for advice. These findings reveal that a low knowledge base in finance can translate into low engagement in information search which might further increase the risk of low decision quality. The study links these findings to the debate on consumer empowerment and discusses implications for the financial services industry.
Keywords: C91; G02; D83; 330; financial literacy; information acquisition; decision making; experiment